2016
DOI: 10.1002/asia.201501381
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Responses of Polygonal Poly(ethylene glycol) Analogues

Abstract: As a new type of topological poly(ethylene glycol) (PEG) analogue, a series of polygonal PEGs with digonal to hexagonal structures were developed. Polygonal PEGs with structures between the digonal and tetragonal types showed molecular-level dispersion in water at 20 °C, whereas the pentagonal and hexagonal PEGs aggregated, which is suggestive of enhanced hydrophobicity by ring expansion. Heating induced conformational changes in the polygonal PEGs and increased their hydrophobicity. Among the polygonal PEGs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Specifically, owing to the high water solubility, low toxicity and antigenicity, and thermal responsivity of PEGs, they have been widely used to increase the water solubility of peptides and proteins, improve their cellular internalization, prolong their blood circulation time, , facilitate their condensation and separation and crystallization, , control their adsorption, suppress their aggregation, , and accelerate their refolding. However, only polydisperse PEGs , with relatively high molecular weights have been used to date. Recent studies have suggested that the physicochemical properties of PEGs depend strongly not only on their molecular weights and topology but also on whether or not they are confined in nanospaces. , …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, owing to the high water solubility, low toxicity and antigenicity, and thermal responsivity of PEGs, they have been widely used to increase the water solubility of peptides and proteins, improve their cellular internalization, prolong their blood circulation time, , facilitate their condensation and separation and crystallization, , control their adsorption, suppress their aggregation, , and accelerate their refolding. However, only polydisperse PEGs , with relatively high molecular weights have been used to date. Recent studies have suggested that the physicochemical properties of PEGs depend strongly not only on their molecular weights and topology but also on whether or not they are confined in nanospaces. , …”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, an oligoethylene glycol chain responses to temperature elevation to increase the hydrophobicity by a conformational change. [41][42][43][44][45][46][47][48][49] Such a thermal response of the TEG chains in bola-AkDPA to increase the hydrophobicity likely promotes the self-assembly in a bilayer membrane. Under the optical microscopic observations of GUVs DOPC$bola-AkDPA (90/10), uorescent domain formation was not observed during heating and cooling processes between 25 and 60 C, and the spherical morphology of the GUV was essentially unchanged without showing budding or membrane deformation (Fig.…”
Section: Self-assembly Of Bola-akdpa In Bilayer Membranementioning
confidence: 99%